2021
DOI: 10.1108/ijchm-11-2020-1256
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anthropomorphic features of artificially intelligent service robots on consumer acceptance: moderating role of sense of humor

Abstract: Purpose This study aims to investigate the impact of both physical and personality-related anthropomorphic features of an artificial intelligence service robot on the cognitive and affective appraisals and acceptance of consumers during service delivery. Design/methodology/approach The proposed hypotheses that investigate the effects of service robots’ physical appearance on the emphasis consumers place on each evaluation criteria they use in determining their willingness to accept the use of service robots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 59 publications
4
49
1
Order By: Relevance
“…As described earlier, entertainment can be defined as the act of amusing or entertaining people. Zhang et al [ 53 ] suggested robots should be augmented to have the ability to make humorous responses and use witty language in order to improve entertainment services. That is, robots should be able to engage in humorous language when interacting with consumers rather than just a typical service language.…”
Section: Discussionmentioning
confidence: 99%
“…As described earlier, entertainment can be defined as the act of amusing or entertaining people. Zhang et al [ 53 ] suggested robots should be augmented to have the ability to make humorous responses and use witty language in order to improve entertainment services. That is, robots should be able to engage in humorous language when interacting with consumers rather than just a typical service language.…”
Section: Discussionmentioning
confidence: 99%
“…Third, while prior research has focused mostly on service robot attributes such as anthropomorphism (Zhu and Chang, 2020), warmth (Zhang et al , 2022), sense of humor (Zhang et al , 2021), interactivity (Shin and Jeong, 2020) and innovativeness (Cha, 2020), our study represents an initial attempt to unveil consumers’ personal characteristics. This allows us to distinguish individuals who are willing to pay a price premium for robotic restaurants from those who are not.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of robot design (e.g. facial features, color, shape, size, voice), humanoid appearance and social/emotional characteristics can influence robot adoption and service experiences (Tung and Law, 2017;Zhang et al, 2021). Based on the uncanny valley theory, a body of HTM and BM research found positive impacts of anthropomorphism on robotics adoption (Zemke et al, 2020;Zhu and Chang, 2020), while some research found its negative impacts IJCHM 34,6 (Akdim et al, 2021;Christou et al, 2020).…”
Section: Robot Research and Future Researchmentioning
confidence: 99%